Identification of a Sensitive Human Immunological Target of Aryl Hydrocarbon Receptor Activation: CD5+ Innate-Like B Cells - Blevins, Lance K.; Zhou, Jiajun; Crawford, Robert B.; Kaminski, Norbert E. (Frontiers in Immunology, 2021)
Xenobiotic-mediated activation of the aryl hydrocarbon receptor (AHR) is immunotoxic in a number of immune cell types, with the B cell being a well-established sensitive target. Recent advances have provided evidence that the B cell repertoire is a heterogeneous population, with subpopulations exhibiting vastly different cellular and functional phenotypes. Recent work from our laboratory identified the T cell specific kinase lck as being differentially regulated by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), which is a potent activator of AHR. While LCK is primarily expressed in T cells, a subset of CD5+ B cells also express LCK. CD5 positivity describes a broad class of B lymphocytes termed innate-like B cells (ILBs) that are critical mediators of innate immunity through constitutive secretion of polyvalent natural immunoglobulin M (IgM). We hypothesized that CD5+ ILBs may be sensitive to AHR-mediated immunotoxicity. Indeed, when CD5+ B cells were isolated from the CD19+ pool and treated with TCDD, they showed increased suppression of the CD40 ligand-induced IgM response compared to CD5- B cells. Further, characterization of the CD5+ population indicated increased basal expression of AHR, AHR repressor (AHRR), and cytochrome p450 family 1 member a1 (CYP1A1). Indeed the levels of AHR-mediated suppression of the IgM response from individual donors strongly correlated with the percentage of the B cell pool that was CD5+, suggesting that CD5+ B cells are more sensitive to AHR-mediated impairment. Together these data highlight the sensitive nature of CD5+ ILBs to AHR activation and provide insight into mechanisms associated with AHR activation in human B cells.